Advantages and Limitations of Nanomaterials in Restorative and Endodontic Treatments: A Literature Review - Mochammad Taha Ma’ruf; Atia Nurul Sidiqa; Ilma Yudistian (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Nanotechnology has transformed dentistry by introducing nanomaterials with superior mechanical properties, improved aesthetics, and enhanced antibacterial effects, thereby improving treatment outcomes. These materials have been widely adopted in modern dental treatments. However, concerns remain regarding their potential toxicity, production costs, and long-term effects on human health and the environment. This review explores the benefits and challenges of nanomaterials in dentistry, particularly their applications in restorative and endodontic treatments. It examines potential risks to provide a balanced perspective on their clinical use. Review: Nanomaterials enhance the strength and durability of dental restorations while reducing bacterial adhesion. In endodontics, nanomaterials enhance the antimicrobial activity and penetration of root canal sealers, thereby improving root canal disinfection and reducing the risk of reinfection. However, prolonged exposure to nanomaterials raises concerns about biocompatibility, oxidative stress, immune responses, and neurotoxicity. Current studies highlight the need for standardized safety protocols and long-term clinical trials. Conclusion: Nanotechnology offers significant advancements in dentistry, improving treatment durability and patient outcomes. However, further research is required to assess long-term safety, optimize materials for clinical use, and develop regulatory guidelines. Ensuring the biocompatibility and environmental safety of nanomaterials is a priority for their widespread adoption.